Vestibular Hair Cells Require CAMSAP3, a Microtubule Minus-End Regulator, for Formation of Normal Kinocilia - O’Donnell, Josephine; Zheng, Jing (Frontiers in Cellular Neuroscience, 2022)
Kinocilia are exceptionally long primary sensory cilia located on vestibular hair cells, which are essential for transmitting key signals that contribute to mammalian balance and overall vestibular system function. Kinocilia have a ‘9+2’ microtubule (MT) configuration with nine doublet MTs surrounding two central singlet MTs. This is uncommon as most mammalian primary sensory cilia have a ‘9+0’ configuration, in which the central MT pair is absent. It has yet to be determined what the function of the central MT pair is in kinocilia. Calmodulin-regulated spectrin-associated protein 3 (CAMSAP3) regulates the minus end of MTs and is essential for forming the central MT pair in motile cilia, which have the ‘9+2’ configuration. To explore the role of the central MT pair in kinocilia, we created a conditional knockout model, Camsap3tm1d/tm1d, which intends to eliminate CAMSAP3 in the inner ear, olfactory bulb, and kidneys. Immunofluorescent staining of the inner ear demonstrates that CAMSAP3 proteins were removed or significantly reduced in Camsap3tm1d/tm1d mice and that adult Camsap3tm1d/tm1d mice have significantly shorter kinocilia than their WT littermates. Transmission Electron Microscopy showed that Camsap3tm1d/tm1d mice are in fact missing that central MT pair in kinocilia more often than their WT counterparts. In the examination of behavior, adult WT and Camsap3tm1d/tm1d mice performed equally well on a swim assessment, right-reflex test, and evaluation of balance on a rotarod. However, adult Camsap3tm1d/tm1d mice show slightly altered gaits including reduced maximal rate of change of paw area and a smaller paw area in contact with the surface. Although Camsap3tm1d/tm1d mice had no differences in olfaction from their WT counterparts, older Camsap3tm1d/tm1d mice did have kidney dysfunction that deteriorated their health. Thus, CAMSAP3 is important for establishing and/or maintaining the normal structure of kinocilia and kidney function but is not essential for normal olfaction. Our data supports our hypothesis that CAMSAP3 is critical for construction of the central MT pair in kinocilia, and that the central MT pair may be important for building long and stable axonemes in these kinocilia. Whether shorter kinocilia might lead to abnormal vestibular function and altered gaits in older Camsap3tm1d/tm1d mice requires further investigation.